IFRS Adoption and the Posthuman Economy: Financial Reforms, FDI, and Economic Growth in MENA Countries - AL-Tuwaijari, Musatfa Rasim; Abdul Rahman, Mara Ridhuan Bin Che; Ahmad, Azlina; Abdul Rahim, Ruzita (Journal of Posthumanism, 2025)
The research aims to assess the impact of IFRS adoption on economic growth in MENA countries, and further, it aims to investigate the role of the mediating variable FDI in the relationship. The study sample consists of 22 countries in the Middle East and North Africa region during the period 2002-2022. The study reviews the empirical results of the variables of the study using the OLS, DOLS, FMOLS, GMM, and LSDVC. The findings of the study show that countries that have adopted or are gradually implementing IFRS are likely to have higher levels of GDP. The study also finds that there is a positive relationship between the adoption of IFRS and the increase in FDI inflows. This rise is an important factor in improving economic development. Hence, there is a positive relationship between the adoption of IFRS and economic growth, with other influential factors such as FDI. This study adds value to the literature regarding the effects IFRS on economic growth and the existence of factors that may enhance economic growth with the help of FDI in the relationship to assist governments in making their future decisions. The results of this study reveal that accounting should be taken into consideration to enhance economic growth through the adoption of IFRS as a way of creating a better environment for the attraction of FDI.